2020
DOI: 10.1108/rmj-03-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of electronic records management system (ERMS) in the Yemeni oil and gas sector

Abstract: Purpose Identification of factors for electronic records management system (ERMS) adoption is important as it allows organizations to focus their efforts on these factors to ensure success. The purpose of this paper is to identify the factors that influence ERMS adoption in the Yemeni oil and gas (O&G) sector. Design/methodology/approach This paper conducts a systematic literature review (SLR) to extract the most common factors that could facilitate successful ERMS adoption. Information technology (IT) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…According to Mosweu et al (2016), the experience and integrity of the experts play a key role in choosing the essential factors that affect technology adoption. Additionally, these experts' evaluation method has shown encouraging results in previous examinations when applied to identifying factors for the adoption of information systems by different organizations in both developed and developing economies (Boonstra et al, 2014;Gagnon et al, 2012;Gruenhagen & Parker, 2020;Hawash et al, 2020;Mosweu et al, 2016;Mukred et al, 2019;Schneider & Sunyaev, 2016). Therefore, once the preceding was done and the factors that could influence BI adoption were identified, they were sent via e-mail to 15 experts from IT, SMEs and Healthcare fields to assess and endorse the factors and/or suggest the addition or removal of any relevant or irrelevant factors, respectively.…”
Section: Experts' Evaluationmentioning
confidence: 99%
“…According to Mosweu et al (2016), the experience and integrity of the experts play a key role in choosing the essential factors that affect technology adoption. Additionally, these experts' evaluation method has shown encouraging results in previous examinations when applied to identifying factors for the adoption of information systems by different organizations in both developed and developing economies (Boonstra et al, 2014;Gagnon et al, 2012;Gruenhagen & Parker, 2020;Hawash et al, 2020;Mosweu et al, 2016;Mukred et al, 2019;Schneider & Sunyaev, 2016). Therefore, once the preceding was done and the factors that could influence BI adoption were identified, they were sent via e-mail to 15 experts from IT, SMEs and Healthcare fields to assess and endorse the factors and/or suggest the addition or removal of any relevant or irrelevant factors, respectively.…”
Section: Experts' Evaluationmentioning
confidence: 99%
“…The implementation of ERMS systems has been found to increase organizational competencies through improved decision-making capabilities (Luchenski et al, 2012). Multiple authors have found that education organizations benefit from improved decision making processes after the implementation of ERMS systems (Adade et al, 2018; Hawash et al, 2020; Hawash et al, 2019). Thus, this study proposed the following hypothesis:…”
Section: Framework Development and Hypothesis Formulationmentioning
confidence: 99%
“…Such systems are deployed to enhance the efficiency and effectiveness of organisational operations but may suffer from a lack of integration. However, effective and efficient implementation of electronic records is influenced by people, organisations, technology and processes (Abdullah et al, 2019) and environment (Hawash et al, 2020). Abdullah et al (2019) further identify the following factors for successful implementation of electronic records: competency and commitment, governance, culture and strategic planning, technology infrastructure and effective implementation.…”
Section: Rmj 321mentioning
confidence: 99%